Peer Review as a Tool for Telecommunication Studies Teaching During COVID. - Muñoz-Gallego, Antonio Jesús; Moreno-Sáez, Rafael Jesús; Fortes-Rodríguez, Sergio; Serrano-Aguilera, Juan José; Mercade-Mele, Pere; Martín-Fernández, Cristian (My University, 2021)
The consequences of COVID-19 have had an impact on all sectors, in particular on education. During the last academic year, different teaching methodologies have been applied, many of them of technological nature, in order to mitigate the adverse effects caused by COVID-related confinements. In this paper, we present the implementation of an experience based on peer reviewing in a Telecommunication degree at the University of Málaga. This experience is part of an educational innovation project, and as a useful tool, one of the reasons is that it can be applied in different teaching scenarios. In this work, peer review has been implemented in two semesters of the same subject, belonging to the same degree in two consecutive years, one preCOVID and the other during COVID. Hence, a detailed assessment is provided in order to decipher possible unknowns about the impact that the pandemic may have had on the learning of our students.
Keywords: Investigación activa en educación; Peer review; Educational innovation